“I Mean You Can Stop. I Already Understand You”: Head Tilts during Conversations - Nyak Mutia Ismail; Veni Nella Syahputri (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
This study tried to shed light specifically on head gestures which are categorized as upward tilts, downward tilts, leftward tilts, rightward tilts, nods, shakes, and turns. This study is qualitative in nature since the data quality is considered as the focal importance in generating the results as well as the conclusions. The data collection was carried out through observation and interviews involving 2 respondents in two different topic rounds. Hence, the instruments are observation sheets, documentations, and interview guides. The data from observation (in the form of videotapes) were analyzed using visual thematic coding, while the interview data were analyzed using interactive analysis. The results unveil that in argumentation topic, repondents tend to perfomr more turning head movement, both right turn and left turn. Meanwhile, in discussion topic, the respondents performed more of nodding and upward tilt. It can be concluded that head movements performed by interlocutors depend on the types o topic(s) they are engaged in. It implies that in teaching and learning process, teachers can use this onformation to ensure the situation during material explanation to see whether the students agree, disagree, understand, or confused with the explanations.